A hospital-based study of hysteroscopic and laparoscopic findings in infertility cases among rural and urban female population of southern Rajasthan - Sharma, Deepika; Sen, Sangeeta; Bilwal, Bharat; Patidar, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Infertility affects millions worldwide and presents significant medical and psychological challenges. This study assesses the diagnostic role of hysteroscopy and laparoscopy in infertile women from rural and urban Southern Rajasthan. Methods: A hospital-based descriptive study of 130 women aged 21-40 years with infertility (primary or secondary) was conducted. All patients underwent diagnostic hysteroscopy and laparoscopy with Chromopertubation. Data was analyzed using Jamovi software. Results: 62.5% had primary infertility, 37.5% had secondary. Laparoscopy revealed ovarian pathology in 56.25%, tubal in 48.34%, uterine in 15.62%, and adhesions in 18.75%. Hysteroscopy revealed uterine abnormalities in 12.5%. Conclusions: Combined hysteroscopy and laparoscopy enhance the diagnosis of female infertility and help guide treatment, “especially in underserved populations”.